GREEN TECHNOLOGY IN IMPROVING DEFECT MANAGEMENT MODEL FOR OPERATED HERITAGE BUILDINGS IN MALAYSIA– A LITERATURE REVIEW - Ahmad Mu’az; Mohd Azian Zaidi; Nur Azfahani Ahmad (Journal of Islamic, Social, Economics and Development, 2021)
Heritage buildings are prone to many issues related to humidity, such ascondensation, lack of air circulation, mould growth and poor air quality that will affect thebuilding life span. At the moment, more than 300 heritage buildings in Malaysia are exposedto these conditions, whilst still maintained conventionally. In conjunction with the MalaysiaScience, Technology, Innovation and Economy (MySTIE), the Shared Prosperity Vision 2030(SPV 2030) and the United Nation Sustainable Development Goals (SDGs), it is significant toestablish sustainable heritage buildings through various efforts of defect management models.However, at present, these models are lacking in finding the significant solutions in controllingdefect issues that are related to internal-humidity conditions for heritage buildings thatempowered by green technologies. Most of the defect management models found in Malaysiaare related to typical procedures and generic documentation. Relevant to the Fourth IndustrialRevolution (IR 4.0), Malaysia have significant potential in establishing a new defectmanagement model that can be linked with green technologies. Since Malaysia receivesabundant energy from solar, initiating green technologies which based from solar energy is highly recommended. This can be an alternative for providing energy for relevant mechanismin improving defect based-humidity, such as ventilators or turbines. This research tries toexplore the key factors on how these green technologies can help to associate and improvedefect management techniques in heritage buildings. Through literature review, it will focus onheritage buildings that have significant defect issues in order to formulate a significant defectmanagement model that can be integrated with green technologies. Ideally, this model can beused by the Government to establish a more sustainable heritage buildings and ultimately,improved the defect management models in Malaysia that are relevant to IR 4.0.